2017
DOI: 10.1038/s41467-017-01562-9
|View full text |Cite|
|
Sign up to set email alerts
|

Transcribed ultraconserved region 339 promotes carcinogenesis by modulating tumor suppressor microRNAs

Abstract: The transcribed ultraconserved regions (T-UCRs) encode long non-coding RNAs implicated in human carcinogenesis. Their mechanisms of action and the factors regulating their expression in cancers are poorly understood. Here we show that high expression of uc.339 correlates with lower survival in 210 non-small cell lung cancer (NSCLC) patients. We provide evidence from cell lines and primary samples that TP53 directly regulates uc.339. We find that transcribed uc.339 is upregulated in archival NSCLC samples, func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 60 publications
(61 reference statements)
4
42
0
Order By: Relevance
“…Up to now, the biological function and mechanism of circRNAs still need to be explored in malignancies progression [19]. Highly conserved sequences and particular covalently closed circular construction formed the feature of circRNAs [20]. It was reported that cir-cRNAs might be the underlying biomarkers to diagnose and cure a series of diseases due to the considerable functions they exerted on the development of diverse diseases, such as cancers [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the biological function and mechanism of circRNAs still need to be explored in malignancies progression [19]. Highly conserved sequences and particular covalently closed circular construction formed the feature of circRNAs [20]. It was reported that cir-cRNAs might be the underlying biomarkers to diagnose and cure a series of diseases due to the considerable functions they exerted on the development of diverse diseases, such as cancers [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new type of RNA:RNA interaction was described involving a T-UCR. The transcript of uc.339 harbors three IEs for miR-339-3p, miR-663b-3p, and miR-95-5p; of note, the uc.339 interaction with these miRNAs leads to up-regulation of their common target CCNE2, the cyclin E2 that plays a role in cell cycle G1/S transition and promotes lung carcinogenesis (Vannini et al 2017), overriding a canonical competing endogenous RNA (ceRNA)-type of interaction (Poliseno et al 2010;Cesana et al 2011) in which overexpression of the lncRNA or of the miRNAs down-regulates the interacting counterpart. Conversely, while up-regulation of uc.339 reduces the levels of miR-339, miR-663b, and miR-95, modulation (both up-and down-) of these three miR-NAs does not significantly affect the expression levels of the uc.339 transcript.…”
Section: Ses Entrap Mirnas Within Lncrna 3-dimensional Structuresmentioning
confidence: 99%
“…These sequences represent a particular type of SE. The disruption of the TREs impairs the binding of miR-339, miR-663b, and miR-95 to uc.339 (Vannini et al 2017). TREs are likely to be present in other lncRNAs and mRNA.…”
Section: Ses Entrap Mirnas Within Lncrna 3-dimensional Structuresmentioning
confidence: 99%
“…For example, non-coding RNA such as microRNAs, small RNA molecules of~22 bp, display a pleiotropic activity by canonically binding thousands of complementary mRNA transcripts and, in turn, perturbing their stability and subsequent translation [35,36]. Other involved mechanisms are the long non-coding RNAs (lnRNAs) that may serve as adaptors to drive epigenetic modulators or may sequestrate epigenetic complexes or transcription factors away from the chromatin [37,38] (Figure 1).…”
Section: Molecular Mechanism Of Epigenetic Modificationsmentioning
confidence: 99%